The contribution of the HIV specialist nurse to HIV care: a scoping review. Issue 23 (17th October 2013) - Tunnicliff, Sarah A; Piercy, Hilary; Bowman, Christine A; Hughes, Charlie; Goyder, Elizabeth C
Abstract : Aims and objectives: To systematically identify and critically examine the evidence of the contribution of the HIV nurse specialist to provision of HIV care in the UK and other developed countries. Background: The HIV clinical nurse specialist role has evolved over the past two decades in response to changes in two areas of HIV care: first, changes in the treatment and care of those with HIV and second, changes and development in advanced nursing practice. The challenges facing HIV care require the development of innovative services including a greater contribution of HIV specialist nurses. A review of current evidence is required to inform developments. Design: A review. Methods: A broad search strategy was used to search electronic databases. Grey literature was accessed through a variety of approaches. Preference was given to UK literature with inclusion of international publications from other developed countries where relevant. Results: Fourteen articles were included. Four themes were identified: the diversity of the clinical role; a knowledge and skills framework for HIV nursing practice; the education and training role of the HIV nurse specialist; and the effectiveness of the HIV nurse specialist. The findings mainly focus on the clinical aspects of the role with little evidence concerning other aspects. There is limited evidence to indicate clinical effectiveness. Conclusions: HIV care is facing substantial challenges, and there is a clear need to develop effective and efficient services, including expanding the contribution of HIV nurse specialists. Such developments need to occur within a framework that optimises nursing contribution and measures their impact on HIV care. This review provides a baseline to inform such developments. Relevance to clinical practice: This review of the literature details current understanding of the role of HIV specialist nurses and the contribution that they make to HIV care.